Analisis Bauran Pemasaran (Marketing Mix) Terhadap Keputusan Pembelian Produk Kopi PT. Tiara Global Coffee Di Aceh Tengah - Nailul Fitri Annisa; Khumaira, S.P, M.Si; Sri Fitri, S.P, M.Si (Departemen Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala associated with AAI (Asosiasi Agribisnis Indonesia). Jl. Tgk. Hasan Krueng Kalee No. 3, Kopelma Darussalam, Banda Aceh, 23111, Indonesia. Email: agrisep@usk.ac.id, 2026)
Coffee is a plantation commodity that plays a significant role in the Indonesian economy. Coffee is a crop cultivated by the people of Aceh, particularly in Central Aceh. PT Tiara Global Coffee produces various types of Arabica and Robusta coffee, from harvesting to production, from upstream to downstream, and into packaged products. This study aims to analyze the influence of the marketing mix (product, price, place, and promotion) on purchasing decisions for PT. Tiara Global Coffee's coffee products in Central Aceh. PT. Tiara Global Coffee implements a marketing strategy based on the 4Ps concept. The method used was descriptive quantitative, and the sampling technique used was random sampling with 37 respondents. The analytical model used in this study was a Likert scale and multiple linear regression. Based on the likert scale analysis of the two research variables, it can be concluded that in the marketing mix variables, product contributed 83.78%, price 74.05%, production 81.44%, and place/distribution 81.44%. The product indicator achieved the highest percentage, thus concluding that consumers perceive the products offered as meeting basic needs. The analysis then yielded a multiple linear regression equation. This equation means that if all independent variables were zero, the purchasing decision would be at 9.352. Positive coefficients for all variables indicate that an increase in each aspect of the marketing mix would lead to an increase in purchasing decisions. Product had the largest coefficient (1.341) and was significant, making it a top priority in PT Tiara Global Coffee's marketing strategy. Therefore, it can be concluded that the product indicator in the marketing mix aspect has a very high influence on purchasing decisions. Keywords: Marketing mix, Purchasing decisions, Coffee, PT. Tiara Global Coffee